Characterization of South Indian rice accessions for physico-chemical properties, starch digestibility and antioxidant properties: Physicochemical and functional properties of pigmented rice - M, Febina; Raman, Maya (ORYZA-An International Journal of Rice, 2025)
Pigmented rice accessions are renowned for their unique colour characteristics and therapeutic applications. This study aims to characterize five popular pigmented rice accessions from South India-Matta (brown), Rakthasali, Njavara, Mappilai samba (red), and Kavuni (black)-by evaluating their physicochemical properties, starch digestibility, and antioxidant properties. The investigation included a detailed analysis of phytochemical concentrations, such as total phenolic content (TPC), total flavonoid content (TFC), and anthocyanins. Antioxidant activities were assessed using the 2,2-Diphenyl-1-picryl hydrazyl (DPPH) free radical scavenging assay, 2,2-Azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) free radical scavenging assay, and ferric reducing antioxidant potential (FRAP) assay. In terms of starch digestibility and glycemic potential, all rice accessions exhibited an intermediate glycemic index (GI) ranging from 55 to 60. Kavuni rice, with a GI value of 60, showed the highest glycemic potential, likely due to its low amylose concentration (6%). All accessions demonstrated significant phytochemical concentrations and notable antioxidant potential. Specifically, Kavuni rice exhibited high levels of TPC (1.4 mg GAE/g), TFC (9.6 mg QE/g), and anthocyanins (0.7 mg CE/g). The high antioxidant activities observed in Kavuni (DPPH - 86.8%; ABTS - 91%; FRAP - 0.5 mg AAE/g) are attributed to its elevated bioactive compound levels. The findings underscore the health-promoting potential of pigmented rice, especially in managing diabetes and related disorders. Future research should explore the molecular mechanisms underlying the health benefits of pigmented rice, particularly in metabolic disorder management. Additionally, breeding programs could aim to enhance specific phytochemical profiles to maximize therapeutic potential.